Collaborative Learning in Virtual Learning Environment using Social Network Analysis - Fitria Amastini; Cristin Kaunang; Afifah Nefiratika; Dana Indra Sensuse; Sofian Lusa (IAES Indonesia Section, 2020)
Distance learning is supposed to provide not only independent learning activities but also two-way interaction and collaborative learning based on inquiry model to control students' learning. E-learning is one of the platform to implement two-way interaction and inquiry model. Universitas Terbuka (UT) is the first open distance education university in Indonesia. This paper will study and visualize participation in discussion and interaction on the virtual learning environment (VLE) UT using Social Network Analysis (SNA). This paper also used a questionnaire to detect knowledge sharing behavior (KSB) in the Collaborative Learning Environment (CLE) based on Social Presence, Perceived Online Attachment Motivation, Perceived Online Relationship Commitment, and Altruism indicators. For the perception of students and evaluation about e-learning UT, we use Yilmaz's Transactional Distance. The results of the measurement network in forum discussion can detect that the tutors are most important, and who are mostly reply to other student's posts or which students' post are mostly commented by others. Personal/Informal network shows that students tend to interact only with students on same location registered region office.